Learning by writing explanations: Is explaining to a fictitious student more effective than self-explaining?. (August 2021) - Lachner, Andreas; Jacob, Leonie; Hoogerheide, Vincent
Abstract: Research has demonstrated that oral explaining to a fictitious student improves learning. Whether these findings replicate, when students are writing explanations, and whether instructional explaining is more effective than other explaining strategies, such as self-explaining, is unclear. In two experiments, we compared written instructional explaining to written self-explaining, and also included written retrieval and a baseline control condition. In Experiment 1 ( N  = 147, between-participants-design, laboratory experiment), we obtained no effect of explaining. In Experiment 2 ( N  = 50, within-participants-design, field-experiment), only self-explaining was more effective than our control conditions for attaining transfer. Self-explaining was more effective than instructional explaining. A cumulating meta-analysis on students' learning revealed a small effect of instructional explaining on conceptual knowledge ( g  = 0.22), which was moderated by the modality of explaining (oral explaining > written explaining). These findings indicate that students who write explanations are better off self-explaining than explaining to a fictitious student. Highlights: We compared writing instructional explanations to self-explaining and retrieval. Self-explaining lead to better test performance than retrieval. Self-explaining was also more effective than instructional explaining. Meta-analytic evidence showed only benefits for oral but not written explaining.